The Role of Artificial Intelligence in Medicine (Modern education and development, 2024)
The integration of Artificial Intelligence (AI) in medicine is revolutionizing healthcare, offering unprecedented opportunities to enhance patient care, streamline clinical processes, and facilitate medical research